2016
DOI: 10.5194/soil-2-49-2016
|View full text |Cite
|
Sign up to set email alerts
|

Tree species and functional traits but not species richness affect interrill erosion processes in young subtropical forests

Abstract: Abstract. Soil erosion is seriously threatening ecosystem functioning in many parts of the world. In this context, it is assumed that tree species richness and functional diversity of tree communities can play a critical role in improving ecosystem services such as erosion control. An experiment with 170 micro-scale run-off plots was conducted to investigate the influence of tree species and tree species richness as well as functional traits on interrill erosion in a young forest ecosystem. An interrill erosio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…Although few studies investigated specifically the impact of weeds on soil erosion, it seems reasonable to assume that similarly to other plant covers, weeds support soil fertility and favour erosion control (Durán Zuazo & Pleguezuelo, ). Plants at ground level reduce splash erosion and reduce runoff velocity (Seitz et al ., ). Roots reduce runoff and erosion by increasing soil shear strength and favouring infiltration (Janeau et al ., ); they also enhance soil stability by direct meshing of soil aggregates (Durán Zuazo & Pleguezuelo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies investigated specifically the impact of weeds on soil erosion, it seems reasonable to assume that similarly to other plant covers, weeds support soil fertility and favour erosion control (Durán Zuazo & Pleguezuelo, ). Plants at ground level reduce splash erosion and reduce runoff velocity (Seitz et al ., ). Roots reduce runoff and erosion by increasing soil shear strength and favouring infiltration (Janeau et al ., ); they also enhance soil stability by direct meshing of soil aggregates (Durán Zuazo & Pleguezuelo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ehrenfeld () and recently Seitz et al . () indicated that changes in soil characteristics directly influence the composition of plant communities, with soil processes responding to the composition of the plant community and vice versa. The possibility that plant‐driven changes in soil processes could create feedback mechanisms that increase the expansion of such species could be vital for the management of expansion (as well as invasion) or the restoration of native communities (Ehrenfeld, ).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned patchy vegetation patterns can be associated with particular soil surface conditions, water redistribution on the soil surface and landscape function, which are often a joint result of natural processes or human activity (Kakembo, 2004). Ehrenfeld (2001) and recently Seitz et al (2016) indicated that changes in soil characteristics directly influence the composition of plant communities, with soil processes responding to the composition of the plant community and vice versa. The possibility that plant-driven changes in soil processes could create feedback mechanisms that increase the expansion of such species could be vital for the management of expansion (as well as invasion) or the restoration of native communities (Ehrenfeld, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…High crown cover reduced soil erosion, whereas it was slightly increased with increased tree height. Thus, low tree stands with a high canopy cover effectively counteract soil loss [50]. Our results illustrate the changes in stand structure and species diversity and provide correlations between stand parameters (mensuration parameters, canopy cover, tree health and vitality structure) in four zones, based on different intensities of water erosion.…”
Section: Discussionmentioning
confidence: 55%